Existimatio como conceito ético em Abelardo - Diebe, Edsel Pamplona (2017)
Peter Abelard (1079-1142) presented two different conceptions about faith (fides) in the Theologia Scholarium: as opinion (existimatio) of things not apparent and as proof (argumentum) of things not apparent. Our thesis is that, despite Abelard understand the faith as existimatio and as argumentum, there is no contradiction between the position defended in ethic and in logic. We tried to solve the problem based on the understanding that Abelard has of human individual in his relation to faith as opinion and as proof. In logic, we will evaluate the individual’s conception based on the relation between the singulars and the universal; and in ethics, we will investigate this notion from the idea of “moral’s intention”. We also propose a brief etymological analysis of term existimatio in its origin of the Roman Law and its ingress in the works of Abelard in 12th century. We will still present the main repercussions that the term has on the discussions of the Council of Sens, in 1140. Finally, we will present three main results about abelardian ethic which we are defenders: a) the ethic is the faith or the belief and as in Augustine, comes before the purely rational understanding; b) the ethic is consent or assent in which the human individual sins according with their intentions; and c) the ethic is free will, for the individual who believes for Abelard is that endowed with existimatio. We argue that this last aspect of abelardian ethic it keep away from the criticism of subjectivism received from the monastic tradition. We maintain, beside this, that the true freedom for Abelard consists in to follow his own will, provided that the same is in accordance with the divine will.